Obesity is associated with fatal coronary heart disease independently of traditional risk factors and deprivation. Issue 7 (14th February 2011) - Logue, Jennifer; Murray, Heather M; Welsh, Paul; Shepherd, James; Packard, Chris; Macfarlane, Peter; Cobbe, Stuart; Ford, Ian; Sattar, Naveed
Abstract : Background: The effect of body mass index (BMI) on coronary heart disease (CHD) risk is attenuated when mediators of this risk (such as diabetes, hypertension and hyperlipidaemia) are accounted for. However, there is now evidence of a differential effect of risk factors on fatal and non-fatal CHD events, with markers of inflammation more strongly associated with fatal than non-fatal events. Objective: To describe the association with BMI separately for both fatal and non-fatal CHD risk after accounting for classical risk factors and to assess any independent effects of obesity on CHD risk. Methods and results: In the West of Scotland Coronary Prevention Study BMI in 6082 men (mean age 55 years) with hypercholesterolaemia, but no history of diabetes or CVD, was related to the risk of fatal and non-fatal CHD events. After excluding participants with any event in the first 2 years, 1027 non-fatal and 214 fatal CHD events occurred during 14.7 years of follow-up. A minimally adjusted model (age, sex, statin treatment) and a maximally adjusted model (including known CVD risk factors and deprivation) were compared, with BMI 25–27.4 kg/m 2 as referent. The risk of non-fatal events was similar across all BMI categories in both models. The risk of fatal CHD events was increased in men with BMI 30.0–39.9 kg/m 2 in both the minimally adjusted model (HR=1.75 (95% CI 1.12 to 2.74)) and the maximally adjusted model (HR=1.60 (95% CI 1.02 to 2.53)). Conclusions: These hypothesis generating data suggest that obesity is associated with fatal, but not non-fatal, CHD after accounting for known cardiovascular risk factors and deprivation. Clinical trial registration: WOSCOPS was carried out and completed before the requirement for clinical trial registration.